Protocol for differentiating cardiomyocytes and generating engineered heart tissues from human feeder-free extended pluripotent stem cells - Zhongjun Wan; Shanshan Wen; Ran Zheng; Li Li; Wei Jiang; Donghui Zhang (STAR Protocols)
Summary: Extended pluripotent stem cells (EPSCs) possess a high differentiation capacity, potentially as a superior seed resource for generating cardiomyocytes. Here, we present a protocol for generating feeder-free EPSCs (ffEPSCs), cardiomyocytes, and engineered heart tissues (EHTs). We describe steps for converting human embryonic stem cells or induced pluripotent stem cells (ESCs/iPSCs) into ffEPSCs, followed by their long-term maintenance, cryopreservation, seed preservation, and differentiation into cardiomyocytes. We then detail procedures for constructing and culturing three-dimensional EHTs followed by their contraction force measurement and optical mapping.For complete details on the use and execution of the protocol, please refer to Zheng et al.1 and Li et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.